2014
DOI: 10.1557/mre.2014.9
|View full text |Cite
|
Sign up to set email alerts
|

Surface engineering for phase change heat transfer: A review

Abstract: Among numerous challenges to meet the rising global energy demand in a sustainable manner, improving phase change heat transfer has been at the forefront of engineering research for decades. The high heat transfer rates associated with phase change heat transfer are essential to energy and industry applications; but phase change is also inherently associated with poor thermodynamic efficiencies at low heat flux, and violent instabilities at high heat flux. Engineers have tried since the 1930's to fabricate sol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
195
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 324 publications
(205 citation statements)
references
References 325 publications
0
195
0
Order By: Relevance
“…5 AFPs in fish living in polar climates can depress body fluid freezing down to −2°C, and AFPs in insects can prevent freezing down to temperatures of as low as −10°C. 5 The antifreezing character of AFPs is explained by several factors: (1) They have a high affinity for the water-ice front (liquid−solid interface). (2) They have an excellent structural match to the ice crystal, which inhibits the growth of the ice front.…”
Section: Ice Nucleation Considerations: Towardmentioning
confidence: 99%
“…5 AFPs in fish living in polar climates can depress body fluid freezing down to −2°C, and AFPs in insects can prevent freezing down to temperatures of as low as −10°C. 5 The antifreezing character of AFPs is explained by several factors: (1) They have a high affinity for the water-ice front (liquid−solid interface). (2) They have an excellent structural match to the ice crystal, which inhibits the growth of the ice front.…”
Section: Ice Nucleation Considerations: Towardmentioning
confidence: 99%
“…[30,[95][96][97][98][99][100] Condensation has two basic modes: filmwise condensation in the case of hydrophilic surfaces, where the condensate exists in the form of a continuous liquid film, and dropwise condensation in the case of hydrophobic surfaces, which is characterized by the dynamic self-renewal of discrete drops. [99] It has been reported that dropwise condensation results in more efficient energy transport, allowing a heat-transfer coefficient that is 5-7 times higher than that of filmwise condensation, since discrete drops have relatively lower thermal resistance than continuous liquid films and can release a larger number of bare sites for nucleation and thermal energy transport.…”
Section: Enhanced Heat Transfermentioning
confidence: 99%
“…Today much attention is paid to development of the methods of heat transfer enhancement at boiling and increasing the critical heat flux [1]. One of directions is the study of the influence of various nanocoatings on heat transfer intensity.…”
Section: Introductionmentioning
confidence: 99%